AGRESIVITAS REMAJA DITINJAU DARI KOMUNIKASI INTERPERSONAL ORANG TUA PADA SISWA-SISWI SMA YOS SUDARSO MEDAN - Selly, Selly; Atrizka, Diny (Jurnal Psikologi : Media Ilmiah Psikologi, 2020)
This study aimed to determine the relationship between parental interpersonal communication and aggressiveness in adolescent. The hypothesis of this study stated that there was a negative relationship between parental interpersonal communication and aggressiveness in adolescent with the assumption the higher parental interpersonal communication, the lower the aggressiveness in adolescent and the lower the parental interpersonal communication, the higher the aggressiveness in adolescent. The subjects of the study are 139 students at Yos Sudarso Medan. Data were obtained from scales to measure parental interpersonal communication with aggressiveness in adolescent. The calculation was done by conducting prerequisite test analysis (assumption test) consisting of normality test and linearity test. The analysis of the data was performed using Product Moment correlation with SPSS 20 for Windows. The results of data analysis showed that the correlation coefficient was -0,696 with significance value with p=0.000 (p <0.05). It showed that there was a negative relationship between parental interpersonal communication and aggressiveness in adolescent. The results of this study indicated that the contribution given parental interpersonal communication variables on aggressiveness in adolescent was by 48,4 percent and the remaining 51,6 percent influenced by other factors not examined. Based on these results, it can be concluded that the hypothesis was accepted, there was a negative relationship between parental interpersonal communication and aggressiveness in adolescent.